Product Competitiveness and the Need for Improving Technologies in Enterprises of the Plastics Industry - Monika GÓRSKA; Renata CABAN (Communications of International Proceedings, 2021)
The main aim of this paper was to present the need for improvement in the field of plastics processing technology in the enterprises selected for the research in the context of their competitiveness. The paper presents the characterization of this sector, its importance for the Polish economy, and analyzes the innovative activity of enterprises manufacturing polymer products. For this purpose, data from national and European statistics were collected, presented, and complemented by a survey carried out on a group of 102 enterprises in the sector. The results were presented for all groups of the enterprises surveyed, indicating their needs and the reasons they are guided by when making decisions on improvements. One of the basic factors mentioned by the enterprises surveyed that determine the quality and thus the competitiveness of a given product is the technology of its production. Since the injection molding technology appeared to be one of the most frequent problems faced by the enterprises, the research was carried out to analyze the effect of injection molding parameters on mechanical and thermal properties and shrinkage of the polymer and polymer composite materials. The choice of the right injection molding parameters directly affects the quality of the products. Monitoring of the injection molding process allows for the achievement of high quality of molded pieces and process repeatability. Therefore, plastics enterprises should constantly strive to improve injection molding technologies.
Keywords: Technology; Improvement; Plastics Industry; Injection Molding Process.